EFEKTIVITAS METODE KIBAR DALAM PEMBELAJARAN AL-QUR’AN PADA TAMAN PENDIDIKAN AL-QUR’AN - Elvi Rahmi (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2019)
Kibar method is a method formulated applicative and effective, so that makes it easy for children to be able to read the Qur'an with a fast, smooth and fluent. As fast as defined in kibar method is within a short time the child is able to read al-qu'an and achieve certain targets. While fluent in question is a child can read the Qur'an without spelled. While fluent means that children can be smoothly and quickly in reading al-qu'an accordance with makharijul letters.